PEGylated Cisplatin Nanoparticles for Treating Colorectal Cancer in a pH-Responsive Manner - Wei Li; Yongjun Sun; Jian Chen; Zhibin Jiang; Jinbao Yang (Journal of Immunology Research)
Colorectal cancer (CRC) is a common malignant tumor, and its incidence ranks third and mortality rate ranks second in the world. Cisplatin cannot target CRC cells and has notable toxicity, which significantly limits its clinical application. The emerging PEGylated nanodrug delivery system can improve circulation time and enhance tumor targeting. In this study, the HA-mPEG-Cis NPs were synthesized by self-assembly, which can target CD44-positive CRC cells and dissolve the PEG hydration layer responsive to the weakly acidic tumor environment. The average hydrodynamic diameter of HA-mPEG-Cis NPs was 48 nm with the polydispersity index of 0.13. The in vitro cisplatin release was in a pH-responsive manner. The HA-mPEG-Cis NPs group showed the highest apoptosis rate (25.1%). The HA-mPEG-Cis NPs exhibited antitumor efficacy via the PI3K/AKT/mTOR signaling pathway. The HA-mPEG-Cis NPs showed the lowest tumor volume and weight among all the groups in CT26 cell-bearing mouse model. The HA-mPEG-Cis nanodrug delivery system not only increases the stability and circulation time but also reduces the side effects of loaded cisplatin. Overall, the in vitro and in vivo experiments confirmed the satisfied antitumor efficacy of HA-mPEG-Cis NPs. Therefore, this study provides a rational design for application of pH-responsive HA-mPEG-Cis nanodrug delivery system in the future.